Provision and Utilization of Team- and Community-Based Operative Care for Patients With Cleft Lip/Palate in North Carolina. (November 2020) - Le, Elliot; Shrader, Peter; Bosworth, Hayden; Hurst, Jillian; Goldstein, Benjamin; Drake, Amelia; Wood, Jeyhan; David, Lisa R.; Runyan, Christopher M.; Vissoci, Joao Ricardo Nickenig; Harker, Matthew; Allori, Alexander C.
Objective: To characterize operative care for cleft lip and/or palate (CL/P) based on location (ie, from American Cleft Palate Craniofacial Association [ACPA]–approved multidisciplinary teams or from community providers). Design: Cross-sectional analysis of Healthcare Cost and Utilization Project State Inpatient Database and State Ambulatory Surgery & Services Database databases for North Carolina from 2012 to 2015. Setting/Patients and Main Outcome Measures: Clinical encounters for children with CL/P undergoing operative procedures were identified, classified by location as "Team" versus "Community, " and characterized by demographic, geographic, clinical, and procedural factors. A secondary evaluation reviewed concordance of team and community practices with an ACPA guideline related to coordination of care. Results: Three teams and 39 community providers performed a total of 3010 cleft-related procedures across 2070 encounters. Teams performed 69.7% of total volume and performed the majority of cleft procedures, including cleft lip repair, palate repair, alveolar bone grafting, and correction of velopharyngeal insufficiency. Community locations principally offered myringotomy and rhinoplasty. Team care was associated with higher guideline concordance. Conclusions: American Cleft Palate Craniofacial Association –approved team-based care accounts for the majority of cleft-related care in North Carolina; however, a substantial volume of cleft-related procedures was provided by community providers, with 3 providers accounting for the vast majority of community cases.